Circular - National Joint Committee for Spanish Relief; Montagu-Pollock, Elizabeth
1940-04-30 038-0040-001 BRITISH COMMITTEE FOR REFUGEES FROM SPAIN AFFILIATED TO THE NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF CHAIRMAN: ELEANOR RATHBONE, M.P. HON. SECRETARY: WILFRID ROBERTS, M.P. ORGANISING SECRETARY: ELIZABETH MONTAGU-POLLOCK HOSPITALITY SECRETARY: JOAN PRIESTLEY 30, ECCLESTON STREET, LONDON, S.W.1. TELEPHONE: SLOANE 9866 April 30th 1940 Our Christmas News Letter made it clear that the European War was going to alter the Spanish Refugee problem in France very seriously, for better or for worse. A new Decreee which will come into force on May 1st 1940 issued by the French Government as an emergency measure because of the desire of France to use her full resources in the annihilation of Nazism, states that all Aliens wishing to reside in France must either find work or be otherwise self-supporting: the State can no longer afford to keep the Camps and Colonies open and unless both men and women can support themselves they must leave France. The local Prefets of Police are however, authorised to grant public assistance to Aliens at their own discretion. It is hard to estimate the practical result of this law. From a legal point of view, provided a Spaniard is in work, he and his family have the right of asylum. During the last three months the men from the large camps have been drafted into work companies under military organisation, leaving the large camps practically empty. This means that thousands of Spaniards are doing manual work for which they receive practically no pay but they are given food and lodging and their families are entitled to an allowance from the Government equal to that given to the families of the French soldier. It is true that the companies have been formed regardless of the mens' qualifications but it is anticipated that, as the great demand for skilled labour becomes apparent and the first effects of the emergency orders subside, those with technical qualifications will be placed in appropriate employment. There are, however, a great number of refugees who have never been in the great camps and many more have been living in small colonies in the interior of France. These too must either find work or leave; emigrating or returning to Spain. Some of the camps will not be closed immediately, for example the womens' and children' quarters in Argeles will remain open: hospitals also will continue and the colonies maintained by voluntary committees will mostly be expanded. The International Commission and other Relief Organisations in France are opening dayschools and creches where women may leave their children during the day while they are at work. The French Catholic Committee has already placed thousands in work and will continue to do so. There will be a limited amount of emigration, plans are being made for expeditions of between 3.000 and 5.000. There is no doubt that this decree will mean a tragedy for many people, but we must remember that the mobilisation in France has placed the whole country on a war basis, and the conditions under which the Spaniards are forced to work are not greatly different from those of millions of Frenchmen. How exactly the decree will work out in practice remains to be seen. Two things are however, clear. First, everybody must get work of some sort and later efforts can be made to place them in 292/946/38/40(I)